O DIÁLOGO ENTRE O ACESSO À JUSTIÇA E O CAPS III - Lusanir de Sousa Carvalho; Rosemary Fonseca Santos; Pedro Wagner Assed Pereira (TRF2, 2018)
This study presents the insertion of a Federal Public Defender together with the multiprofessional team in a group composed of family members and users of a CAPS III device, in view of the increasing number of users who had applications for benefits dismissed by social security in this device. By causing growth in the number of resources with overload to family members in the care of the user. The objective of this work is to discuss the impact of this situation in the perspective of care overload. This research had a qualitative character, made through observation participant in meetings with the family groups during two years, with legal support once every month. Fifteen family members of the CAPS III family group, who had the benefit of continuing care (BPC) canceled and / or those who requested the benefit, were absent for this reason. Of the 15 relatives that the DPU filed a lawsuit, 10 of them were able to review the benefits, 3 of them had the benefit denied and only 2 families had the case filed by the local court. With the inclusion of legal guidance offered to users and their respective families, we see new possibilities for intervention transforming the city's eyes and attitudes towards those suffering from psychological distress, minimizing the impacts presented by the family's overload of care.